Oil price shocks and macroeconomic dynamics in an oil-exporting emerging economy: A New Keynesian DSGE approach - Sunday Oladunni (CBN Journal of Applied Statistics, 2020)
The global oil dynamics has significant implications for both oil exporting and importing small open economies. However, much of the literature on oil shocks is oriented towards advanced oil-importing economies. Micro-founded studies that explore the effects of oil shocks from the standpoint of oil-endowed emerging economies are rather sparse, compared to the preponderance of studies on developed oil importers and exporters. Thus, resulting to a consequential knowledge gap on oil price transmission mechanism and a limited appreciation of the growing policy dilemmas in these economies. The paper, therefore, sets up a new Keynesian dynamic stochastic general equilibrium (DSGE) model to study how an oil price shock impact macroeconomic aggregates in an oil-rich emerging economy. We consider a positive oil price shock to uncover the extent to which oil price increase is positive for the economy. The typical small open economy model is enriched with an export-oriented oil firm, a multi-sector foreign production and a non-oil domestic firm. The model is closed with exchange rate-augmented interest rate rule, and it is calibrated forNigeria, an important oil producer. Macroeconomic responses, sequel to a simulated positive oil price shock, reveal evidence of Dutch disease and the operation of the Harrod-Balassa-Samuelson effect. We find a compelling need for oil-endowed emerging economies to address these phenomena by ensuring a robust non-oil sector with limited exposure to the vagaries of oil price oscillation.
Keywords: E32; F41; F47; Q41; 330; DSGE Model; Emerging Oil Exporter; Macroeconomic Dynamics; Oil Price